2012
DOI: 10.3389/fnagi.2012.00014
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of aging on spatial learning through exploratory navigation and map reading

Abstract: It has been shown that abilities in spatial learning and memory are adversely affected by aging. The present study was conducted to investigate whether increasing age has equal consequences for all types of spatial learning or impacts certain types of spatial learning selectively. Specifically, two major types of spatial learning, exploratory navigation and map reading, were contrasted. By combining a neuroimaging finding that the medial temporal lobe (MTL) is especially important for exploratory navigation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
76
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(89 citation statements)
references
References 59 publications
12
76
1
Order By: Relevance
“…In contrast, in a new environment, the use of a printed map providing an aerial view of the neighborhood seems to be less helpful for older adults than for younger ones (e.g., Goodman et al, 2005;Sjölinder et al, 2005). Recently, however, the opposite result was obtained by Yamamoto and DeGirolama (2012), who showed that some older adults are able to maintain their map-reading skills relatively well in unknown environments.…”
Section: Navigating and Orientatingmentioning
confidence: 76%
“…In contrast, in a new environment, the use of a printed map providing an aerial view of the neighborhood seems to be less helpful for older adults than for younger ones (e.g., Goodman et al, 2005;Sjölinder et al, 2005). Recently, however, the opposite result was obtained by Yamamoto and DeGirolama (2012), who showed that some older adults are able to maintain their map-reading skills relatively well in unknown environments.…”
Section: Navigating and Orientatingmentioning
confidence: 76%
“…Although the current study was not designed to disambiguate the relative contributions of development and/or use of an allocentric representation versus mental spatial transformations in terms of age effects on learning from a map, previous research does suggest age-related impairments in these processes (Devlin & Wilson, 2010; Iaria et al, 2009; Joanisse et al, 2008; Yamamoto & DeGirolama, 2012). …”
Section: Discussionmentioning
confidence: 97%
“…Similarly, older adults evidence deficits on tasks requiring them to traverse routes in one direction after studying a map (e.g., Carelli et al, 2011; Wilkniss et al, 1997). A recent study directly compared the influence of a first-person perspective to a survey perspective for learning a spatial layout (Yamamoto & DeGirolamo, 2012). Greater age-related differences were observed for indicating landmark locations on a 2D representation of the environment after encoding from a first-person perspective than after map study.…”
mentioning
confidence: 99%
“…By comparison, our DI values,~19 for younger participants and~47 for elder participants, were within a range similar to those reported in previous research. Results from reconstruction of object arrays with young participants revealed mean DI values around 20 (Shelton & McNamara, 2005) and between 35 and 65 for map reconstruction by older participants (Yamamoto & Degirolamo, 2012).…”
Section: Reconstruction Task With Bidimensional Regressionmentioning
confidence: 93%